Analisis Pengaruh Job Description Terhadap Kepuasan Karyawan PT. XYZ - Earliawan Muhammad Irbah Zain; Minto Waluyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Job Descriptions contain descriptions of certain jobs that are really needed for all corporate organizations in any industry. The purpose of this research is to find out how the job description influences the job satisfaction of PT XYZ employees. The population in this study were 40 PT XYZ employees as samples. The data collection method was carried out through distributing research instruments and direct observation. Then the data was tested using simple linear regression. Data analysis shows that there is a significant influence between job descriptions and employee job satisfaction. Indicated by a smaller significance value and a larger f count, it can be concluded that the job description variable has an influence on employee job satisfaction.